THE DEFENSIVE–OFFENSIVE POLITICAL BEHAVIOR OF NORTH KOREA IN THE KOREAN PENINSULA - Aucky Adi Kurniawan (The Republic of Indonesia Defense University, 2021)
The study seeks to explain North Korea's political behavior that tends to act defensively and offensively which has often been represented as a dangerous country. Moreover, historically, the events of the Korean War that led to the breakup of Korea into two parts, the northern part that is associated with the Soviet Union and the southern part that is joined by the United States, makes the relationship between the two countries increasingly conflictual. Coupled with the formation of two axes of power since the collapse of the Soviet Union, North Korea is allied with its ideological one brother China, and South Korea is allied with the United States. The political escalation between the two countries continues to rise, resulting in the relationship of two becoming very conflictual, and because of that, the rivalry that is formed between the two countries raises various potential conflicts that couldn't be avoided. This research used the congruent method by used the balance of threat theory from Stephen Walt who argued that the state reacts to the perceived threat rather than power, and aims to balance it. The results found that North Korea's defensive - offensive actions were motivated by distrust of America-allied South Korea through several joint exercise programs on the peninsula that is considered a form of threat. Overall, the main argument of this research is the North Korea’s defensive - offensive actions are determined by the attitudes of South Korea and its ally the United States.